Europeanization and new member states : a comparative social network analysis - Jurje, Flavia (Milton Park, Abingdon, Oxon : Routledge, 2013)
"This book examines the Europeanization of the polity and politics of a new EU Member State. Using social network analysis in a comparative research design, it provides a systematic analysis of the effects of Europeanization on the institutions, policy processes, power constellation and conflict among national elites"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Political culture -- European Union countries; Civil society -- European Union countries; European Union countries -- Politics and government; Electronic books